“Please pay special attention”: creation of infrastructure in settlements in the territory of nomad aliens - I. V. Lidzhieva; Yu. S. Shurguchieva (Nomadic Civilization: Historical Research)
The relevance of the study is dictated by the increased interest in regional history and the growing role of the anthropogenic factor in arid territories. The purpose of this article is to study the problem of the formation of socio-economic infrastructure on the territory of the settled villages of the Stavropol province in the context of the imperial policy of transferring nomadic peoples to settled life. Based on the analysis of documentary materials from the funds of the State Archive of the Stavropol Territory, using the methods of historical anthropology and historical geography, the paperwork documentation of the office of the Stavropol governor and the Department of Nomadic Peoples was examined. The authors pay special attention to the aspect of the expression of the will of the people at public gatherings, recorded in the verdicts passed at them. It was the practice of jointly resolving the main issues of the life of society, transferred from nomadic society, then legalized by the authorities in regulatory legal acts, that allowed nomads to adapt to the conditions of a new way of managing. As a result, the authorities, based on the established practice of nomadic farming, developed measures to organize the socio-economic infrastructure in the settled villages. The study revealed the absence of a clear policy of the imperial authorities on the transfer of nomads to settled life. The very difficult process of introducing nomads to settled life is shown, which led to their ranking into certain groups depending on their material well-being.